2015
DOI: 10.1002/ece3.1664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate on pine processionary moth fecundity and on its egg parasitoids

Abstract: Climate change may be affecting the fecundity of phytophagous insects as well as impacting their natural enemies. However, temperature impacts these two insect groups differently, disrupting population regulation mechanisms, and ultimately, possibly culminating in an outbreak of the host. The pine processionary moth (PPM) is one of the most harmful insects of the Mediterranean basin. Not only are PPM larvae harmful to plants, but they are also dangerous to humans because of their urticating hairs. Although som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(156 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, host tracking is mandatory for specialist parasitoids, but generalist ones could even be present before host arrival, living in alternative hosts (Auger-Rozenberg et al 2015). Previous studies have shown that in areas recently colonized by PPM, the percentage of parasitism is significantly reduced (Alemany et al 1994, Tiberi et al 2015. The conquest of a new habitat could thus be fueled by the lack of natural control against PPM, since egg parasitoids have been repeatedly pointed out as main controller of the PPM populations (Tsankov et al 1996, Zovi et al 2006, Mirchev et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, host tracking is mandatory for specialist parasitoids, but generalist ones could even be present before host arrival, living in alternative hosts (Auger-Rozenberg et al 2015). Previous studies have shown that in areas recently colonized by PPM, the percentage of parasitism is significantly reduced (Alemany et al 1994, Tiberi et al 2015. The conquest of a new habitat could thus be fueled by the lack of natural control against PPM, since egg parasitoids have been repeatedly pointed out as main controller of the PPM populations (Tsankov et al 1996, Zovi et al 2006, Mirchev et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Tiberi et al . (2015), with a 9‐years' time series observed in Monte San Michele, Florence, Italy, the average parasitism varied inter‐annually from 4% to 26%. It was proposed that daily temperatures above 30 °C would explain lower parasitism rates in years with hot summers.…”
Section: Discussionmentioning
confidence: 99%
“…The two major egg parasitoid species found in this study, B. servadeii and O. pityocampae , are the same observed all over the Mediterranean basin, although in variable proportions ( e.g . Schmidt et al ., 1997; Tsankov et al ., 1998; Perez‐Contreras & Soler, 2004; Arnaldo & Torres, 2006; Mirchev et al ., 2010; Tiberi et al ., 2015). In the present study, overall parasitism by B. servadeii was higher than that of O. pityocampae , with some differences on the species proportion among sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations